Unusual presentation of a simple bone cyst in the coronoid process of the mandible with xanthomatous cells - Leite, Adriana Caroline; Dallazen, Eduardo; Ito, Fabio Augusto; Borges, Hedelson Odenir Iecher; Statkievicz, Cristian; Lima, Heliton Gustavo; Takahama-Jr, Ademar (Journal of Oral Diagnosis, 2019)
Simple Bone Cyst (SBC) is an uncommon jaw lesion considered a “pseudocyst” because the lack of epithelial lining. In turn, xanthomatous cells are abnormal macrophages, also called histiocytes, characterized by the abundant presence of lipid content. They are mainly related to a soft tissue injury called xanthoma, but can also be found in pre-existing intraosseous lesions or in intraosseous xanthoma variations. Thus, the objective of this study is to report a case of a 16-year-old male patient, referred with an asymptomatic radiolucent lesion in the right coronoid process. The cone-beam computed tomography confirmed the presence of an osteolytic lesion and an exploratory surgery was indicated. During the surgical procedure, an almost empty cavity was found, with small fragments of soft yellowish tissue, which was removed. The microscopic analysis revealed the pre- sence of xanthomatous cells. After 3 months a total bone healing was noted. Clinical and radiographic follow-up of the case was performed for 1 year, without signs of recurrence. It is very important the association of clinical and histopathological characteristics for the diagnosis, mainly in cases with atypical radiographical, clinical and histopathological presentation.